A non-exercise method to determine cardiorespiratory fitness identifies females predicted to be at 'high risk' of type 2 diabetes. (January 2017) - Gray, Benjamin J; Stephens, Jeffrey W; Turner, Daniel; Thomas, Michael; Williams, Sally P; Morgan, Kerry; Williams, Meurig; Rice, Sam; Bracken, Richard M; ,
This study examined the relationship between cardiorespiratory fitness determined by a non-exercise testing method for estimating fitness and predicted risk of developing type 2 diabetes mellitus using five risk assessments/questionnaires (Leicester Diabetes Risk Score, QDiabetes, Cambridge Risk Score, Finnish Diabetes Risk Score and American Diabetes Association Diabetes Risk Test). Retrospective analysis was performed on 330 female individuals with no prior diagnosis of cardiovascular disease or type 2 diabetes mellitus who participated in the Prosiect Sir Gâr workplace initiative in Carmarthenshire, South Wales. Non-exercise testing method for estimating fitness (expressed as metabolic equivalents) was calculated using a validated algorithm, and females were grouped accordingly into fitness quintiles <6.8 metabolic equivalents (Quintile 1), 6.8–7.6 metabolic equivalents (Quintile 2), 7.6–8.6 metabolic equivalents (Quintile 3), 8.6–9.5 metabolic equivalents (Quintile 4), >9.5 metabolic equivalents (Quintile 5). Body mass index, waist circumference, and HbA1c all decreased between increasing non-exercise testing method for estimating fitness quintiles ( p  < 0.05), as did risk prediction scores in each of the five assessments/questionnaires ( p  < 0.05). The proportion of females in Quintile 1 predicted at 'high risk' was between 20.9% and 81.4%, depending on diabetes risk assessment used, compared to none of the females in Quintile 5. A calculated non-exercise testing method for estimating fitness <6.8 metabolic equivalents could help to identify females at 'high risk' of developing type 2 diabetes mellitus as predicted using five risk assessments/questionnaires.